Adipose tissue, metabolic syndrome, and non-alcoholic fatty liver disease – a short review - Kouis, Panagiotis; Pampaka, Despina; Panayiotou, Andrie (My University, 2014)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease globally, and it is expected to rise even further as a result of the increase in obesity and related risk factors. This short review summarises current evidence on the role of adipose tissue and insulin resistance in NAFLD and the interrelationship between NAFLD and the metabolic syndrome (MetS), considering central adiposity is a major feature of both the MetS and NAFLD, and that NAFLD has been previously described as the hepatic manifestation of the MetS. In addition, genetic studies of NAFLD with relation to adiposity and insulin resistance are reviewed, and up-to-date diagnostic and therapeutic tools are also discussed.
Keywords: NAFLD; Adipose tissue; Insulin resistance; Metabolic syndrome; Genetics of NAFLD